2021
DOI: 10.21203/rs.3.rs-427859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bidirectional Hybrid Optical Communication System Based on Wavelength Division Multiplexing for Outdoor Applications

Abstract: The simulation and investigation of a 32×10 Gb/s WDM all–optical bidirectional hybrid communication system for outdoor applications is presented in this article via multidisciplinary softwares. In order to track the system condition, a strain sensor based on fiber Bragg grating (FBG) is integrated in–line with the fiber optic link (FO–link). Then, a free space optical link (FSO–link) with 4–channel is simulated to act backup or rescue to the FO–link in the event of disaster or bombing. The FO–link is working w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Encryption method based on some emerging techniques such as chaotic systems is one of the essential resources to ensure the protection of such documents. Most of the previous strategies were based on optical code [6][7][8][9] until a chaotic laser emerged that plays an important role in enhancing the security of optical communication [10][11][12][13]. In chaotic communication, the carrier is used to embed the message before sending it to the receiver side.…”
Section: Introductionmentioning
confidence: 99%
“…Encryption method based on some emerging techniques such as chaotic systems is one of the essential resources to ensure the protection of such documents. Most of the previous strategies were based on optical code [6][7][8][9] until a chaotic laser emerged that plays an important role in enhancing the security of optical communication [10][11][12][13]. In chaotic communication, the carrier is used to embed the message before sending it to the receiver side.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies on chaotic communication are limited to one-to-one communication with one pair of chaotic lasers [2][3][4][5][6][7] , which can not meet the development demand of future secure communications. Hence, multi-access optical chaos communication systems based on wavelength division multiplexing (WDM) have been proposed [8][9][10][11][12][13][14][15][16][17][18][19] . For example, Matsuura et al have demonstrated experimentally and numerically WDM with chaotic waveforms as subcarriers in two pairs of one-way-coupled Nd: YVO4 microchip lasers 8 .…”
Section: Introductionmentioning
confidence: 99%